An interface-aware sub-scale dynamics multi-material cell model for solids with void closure and opening at all speeds. (15th August 2020) - Klima, Matej; Barlow, Andrew; Kucharik, Milan; Shashkov, Mikhail
Highlights: New formulation of the IASSD closure model for multi-material ALE computations. Supports solid or fluid materials, void closure and opening at interfaces. Usable for both low and high speed impact simulations (examples are shown). Abstract: We present a multi-material cell model (closure model) for demanding arbitrary Lagrangian-Eulerian (ALE) simulations of fluids and solids. It is based on the interface-aware sub-scale dynamics (IASSD) approach which utilizes the exact material interface geometry within the computational cell to calculate internal material interactions. Our formulation of the closure model also aims to improve the accuracy in low-speed impact events. Voids are used to represent ambient vacuum and internal free boundaries of the distinct materials. Void regions can close and open at contact surfaces, allowing a transition from contact physics to free motion in vacuum. The coupling of void closure and opening with a new formulation of the IASSD model for solids is tested on several one- and two-dimensional numerical examples, ranging from gas expansion in vacuum to planar and round object impacts at various speeds.